"Loving, Knowing Ignorance": A Problem for the Educational Mission of Museums. (April 2016) - Gilbert, Lisa
Abstract: In this essay, I suggest that Mariana Ortega's concept of "loving, knowing ignorance" (2006) provides a useful conceptual tool for museum practitioners who seek to advance a progressive mission. This form of ignorance assumes authority in describing and acting on behalf of a subject, even as it fails to take seriously the subject's self‐knowledge and agency. While Ortega initially coined this term to describe the stance of white feminists toward women of color, here I extend the concept to describe a wider range of knowers—in this case, the institutional museum. Using a case study at the Museum of Fine Arts, Boston to illustrate this problem, I will suggest that becoming aware of instances of loving, knowing ignorance and learning to avoid it is a key skill for museum professionals who hope for their institutions to fulfill their educational mission in a diverse and democratic society.